The Impact of Trading Volume, Leverage, Earning Volatility, Firm Size, and Dividend Yield on Stock Price Volatility - Haikal, Fahri (Politeknik Negeri Ambon, 2025)
This study aims to analyze the factors that influence stock price volatility in consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX). These factors include stock trading volume, leverage, earning volatility, company size (firm size), and dividend yield. The study was conducted in the period 2018–2022, using a sample of 35 companies selected through a purposive sampling method based on certain criteria, namely being registered in the consumer goods industry sector since 2016, always publishing annual financial reports, and not conducting a stock split during the study period. This research is included in the quantitative research category because this research uses empirical quantitative approaches to collect, analyze, and present data along with the results of the research. In this study, the researcher uses a research strategy with an associative approach. The results of the study show that stock trading volume, earning volatility, and firm size have a significant positive effect on stock price volatility, which means that the higher the three variables, the higher the stock price volatility. Conversely, leverage has a significant negative effect, where increasing leverage reduces stock price volatility. Meanwhile, dividend yield does not significantly affect stock price volatility. The shares of companies in the consumer goods industry sector have been proven to be able to generate promising profits. The condition of stock price fluctuations in this sector is also relatively flat. This will increase investor confidence in the fundamentals of companies listed in the consumer goods industry sector. This sector also has a fairly high percentage of market capitalization value.